A low-tcr ultra-low-resistance ruthenium-based resistance paste, a preparation method and use thereof
Patent Information
- Application Number
- CN202311504951.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-13
AI Technical Summary
但现在的电阻器正往高功率方向发展,这意味着其发热量会大大提升,如若膜电阻的电阻温度系数与零值的偏差较大,就会导致电阻器的阻值随温度变化较大,不能应用于高精度电阻器中,尤其是在超低阻电阻器中
[0023]1.钌酸铋的加入会使电阻浆料的方阻值小幅度上升,在所需电阻浆料阻值较大时,钌酸铋可以替代二氧化钌在导电功能相中的作用,在添加质量相同的情况下,钌在钌酸铋中所占质量百分比更小,由此可以节约贵金属钌的用量;
Smart Images

Figure CN117831832B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resistive paste technology, and particularly relates to an ultra-low resistive ruthenium-based resistive paste with low TCR, its preparation method and application. Background Technology
[0002] Integrated circuits are a significant achievement in the development of modern electronic technology, and thick-film hybrid integrated circuits are an important component of integrated circuits. Electron pastes, as fundamental materials for electronic components, are also widely used in thick-film hybrid integrated circuits. Thick-film resistors, as the most important components in thick-film circuits and hybrid integrated circuits, have the earliest development and the most mature manufacturing technology.
[0003] The resistive element of a thick film resistor is a conductive film layer formed by screen printing and subsequent sintering of resistive paste on a substrate such as ceramic, glass, or silicon.
[0004] Film resistors are advantageous for miniaturization of electronic devices due to their good stability, high precision, low noise, good frequency characteristics, wide operating temperature range, and high power consumption per unit area. However, current resistors are developing towards higher power, which means that their heat generation will increase significantly. If the temperature coefficient of resistance of the film resistor deviates significantly from zero, the resistance value of the resistor will change greatly with temperature, making it unsuitable for use in high-precision resistors, especially in ultra-low resistance resistors.
[0005] In existing ultra-low resistance resistive pastes, the conductive functional phases are mainly silver, palladium, and ruthenium dioxide. To obtain a lower total resistance coefficient (TCR) value, a large amount of palladium needs to be added to control the TCR. However, the high value of palladium leads to excessively high costs for ultra-low resistance resistive pastes. Therefore, to reduce costs, base metal oxides such as copper oxide, niobium pentoxide, and tin trioxide, or metal alloy powders such as iron-nickel alloys and copper-nickel alloys, are added. However, the addition of these metal oxides or metals increases the sheet resistance of the resistive paste, which is detrimental to the use of ultra-low resistance resistors. Furthermore, the addition of these metal oxides may react with the ceramic substrate, reducing its wettability and thus weakening the adhesion between the paste and the substrate. To address the shortcomings of existing technologies, a low-TCR, sheet resistance value below 1 Ω / □, and low-cost ultra-low resistance resistive paste is needed to meet the performance requirements of high-precision ultra-low resistance resistor products. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides an ultra-low ruthenium-based resistive paste with low TCR and a sheet resistance value below 1Ω / □, which can be applied to the field of high-precision ultra-low resistance resistors.
[0007] To achieve the above objectives, the present invention provides an ultra-low resistivity ruthenium-based resistive paste with low TCR, comprising, by weight percentage, 50%–65% conductive functional phase, 15%–30% glass binder phase, 1%–5% additives, and 15%–30% organic carrier.
[0008] The conductive functional phase must include silver and palladium, as well as ruthenium dioxide and / or bismuth ruthenate; the particle size of ruthenium dioxide and bismuth ruthenate is <50nm, and the particle size of silver and palladium is <2μm.
[0009] The conductive functional phase comprises, by weight percentage (100%): 85%–95% silver and palladium, and 5%–15% ruthenium dioxide or bismuth ruthenate.
[0010] The composition of the silver and palladium, based on a mass percentage of 100%, is: 50%–70% silver and 30%–50% palladium.
[0011] The glass binder phase comprises, by mass percentage, 15%–90% SiO2, 5%–75% Al2O3, 3%–25% CaO, and 0%–1.5% MgO. The softening temperature of the glass binder phase is 830–870℃, and the particle size is <5μm.
[0012] The additive includes titanium dioxide and any one of copper oxide, silicon and silicon oxide, calcium ruthenium ruthenium tincture, copper ruthenium tincture, and barium bismuthate. Based on a mass percentage of 100%, the additive comprises: 30%–50% titanium dioxide, and 50%–70% of any one of copper oxide, silicon and silicon oxide, calcium ruthenium tincture, copper ruthenium tincture, and barium bismuthate.
[0013] The organic carrier comprises, by weight percentage (100%): 75%–90% organic solvent, 6%–10% thickener, and 1%–5% organic additive.
[0014] The organic solvent is one or more of terpineol, butyl carbitol acetate, and butyl carbitol; the thickener is one or more of ethyl cellulose, alkyd resin, and acrylic resin; and the organic additive is one or more of soybean lecithin, Span-85, and oleic acid.
[0015] Preferably, the conductive functional phase is composed of silver, palladium and bismuth ruthenate.
[0016] Preferably, the additive is composed of titanium dioxide and any one of calcium ruthenate, copper ruthenate, and barium bismuthate.
[0017] Preferably, the additive is composed of titanium dioxide and silicon and silicon oxide.
[0018] A method for preparing a class of low-TCR ultra-low-resistivity ruthenium-based resistive pastes includes the following steps:
[0019] (1) Add the thickener to the main solvent, heat to 80-100℃, stir at 30-60r / min until the thickener is completely dissolved, then add the organic additive, and after complete dissolution, cool to obtain the organic carrier;
[0020] (2) The components of the conductive functional phase and the glass binder phase are mixed and dispersed to obtain a well-dispersed mixed powder; the mixing and dispersion includes: using alcohol as a medium, ball milling at a speed of 250-300 r / min for a time of 60-120 min, followed by filtration, drying, grinding and dispersion.
[0021] (3) The mixed powder is added to the organic carrier and dispersed evenly to obtain the resistive slurry; the even dispersion specifically includes: first pre-mixing in a planetary mixer at 1500-2000 r / min, and then grinding thoroughly to a fineness of less than 5 μm by a three-roll mill.
[0022] The mechanism and beneficial effects of this invention are as follows:
[0023] 1. The addition of bismuth ruthenate will slightly increase the sheet resistance of the resistive paste. When a large resistive paste resistance is required, bismuth ruthenate can replace the role of ruthenium dioxide in the conductive functional phase. Under the same mass addition, the mass percentage of ruthenium in bismuth ruthenate is smaller, thereby saving the amount of precious metal ruthenium used.
[0024] 2. When the metal cations of the introduced ruthenium salts are the same as those in the glass composition (such as calcium ruthenium ruthenium ruthenium ruthenium oxide and calcium oxide in the glass phase), they improve the interfacial properties between the conductive functional phase and the glass binder phase, making the overlap between ruthenium dioxide and bismuth ruthenium ruthenium ruthenium oxide in the conductive functional phase and the glass binder phase closer, achieving a higher degree of matching. At the same time, they can achieve a stronger ability to regulate TCR than general metal oxides (such as copper oxide, zinc oxide, niobium pentoxide, etc.), resulting in a lower TCR value.
[0025] 3. By observing the cross-section (e.g.) Figure 1 ), simulation calculation (such as Figure 2 The study also included energy dispersive spectroscopy (EDS). The presence of silicon and silicon oxide dispersed within the silver-palladium mixture indicated that silicon and silicon oxide could form a solid solution with palladium and silver, improving silver migration at high temperatures and enhancing the thermal expansion of the conductive phase. Furthermore, silicon could react with the alumina substrate to form a transition structure between the conductive phase and the ceramic substrate, better connecting them. This approach not only addresses the thermal expansion matching issue between the resistive element and the ceramic substrate from multiple perspectives but also increases the connection strength between them, reducing the likelihood of circuit slack, short circuits, or open circuits.
[0026] This invention changes the interface bonding between the conductive functional phase and the glass binder phase, and between the conductive functional phase and the ceramic matrix by altering the types and proportions of additives. This effectively reduces the resistance value and TCR, and to a certain extent reduces the cost. It solves the problems of large resistance temperature coefficient and poor matching between the resistive element and the ceramic substrate in ordinary ultra-low resistance resistors, and can be applied to high-precision ultra-low resistance resistor products. Attached Figure Description
[0027] Figure 1 SEM image of the cross-section of the resistive paste of the present invention after sintering.
[0028] Figure 2 : Simulation calculation diagram of the component distribution of the resistive slurry of the present invention. Detailed Implementation
[0029] To make the technical problems actually solved by the present invention, the key technical means to solve the technical problems, and the technical effects clearer, several sets of the described resistive pastes and their preparation methods are further given below through examples and comparative examples. The examples are only used to explain the present invention and do not constitute any limitation on the present invention (the % below all represent mass fractions).
[0030] Example 1
[0031] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, silicon and silicon oxide 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0032] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0033] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0034] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistive slurry of Example 1.
[0035] Example 2
[0036] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, calcium ruthenate 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball-milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0037] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0038] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0039] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistive slurry of Example 2.
[0040] Example 3
[0041] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, copper ruthenate 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0042] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0043] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0044] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistive slurry of Example 3.
[0045] Example 4
[0046] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, barium bismuthate 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0047] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0048] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0049] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistive slurry of Example 4.
[0050] Example 5
[0051] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 53%, palladium 35%, ruthenium dioxide 9%, copper oxide 1%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0052] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0053] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0054] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistive slurry of Example 5.
[0055] Example 6
[0056] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, bismuth ruthenate 8%, silicon and silicon oxide 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball-milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The bismuth ruthenate particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0057] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0058] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0059] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistive slurry of Example 6.
[0060] Comparative Example 1
[0061] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 53%, palladium 35%, ruthenium dioxide 8%, copper oxide 2%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0062] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0063] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0064] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistivity slurry of Comparative Example 1.
[0065] Comparative Example 2
[0066] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 53%, palladium 34%, ruthenium dioxide 8%, copper oxide 3%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0067] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0068] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0069] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistivity slurry of Comparative Example 2.
[0070] Comparative Example 3
[0071] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, zinc oxide 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball-milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0072] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0073] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0074] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistivity slurry of Comparative Example 3.
[0075] Comparative Example 4
[0076] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, niobium pentoxide 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0077] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0078] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0079] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistivity slurry of Comparative Example 4.
[0080] Comparative Example 5
[0081] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, ruthenium dioxide 8%, tin trioxide 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The ruthenium dioxide particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0082] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0083] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0084] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistivity slurry of Comparative Example 5.
[0085] Comparative Example 6
[0086] Preparation of the functional phase: Raw materials were weighed according to the following mass percentages: silver 52%, palladium 34%, bismuth ruthenate 8%, copper oxide 4%, and titanium dioxide 2%. These were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and further ground to disperse the functional phase. The bismuth ruthenate particle size was <50 nm, and the silver and palladium particle sizes were <2 μm.
[0087] Preparation of glass binder phase: Weigh the raw materials according to the mass percentages of SiO2 73%, Al2O3 12%, CaO 14.5%, and MgO 0.5%. Mix the raw materials evenly and place them in a melting furnace at 1500℃ for melting and holding for 2 hours. The resulting mixture is then water-quenched to obtain glass slag. The glass slag is then ground into particles <2μm using a ball mill and dried to obtain the glass binder phase.
[0088] Preparation of organic carrier: Weigh the raw materials according to the following mass percentages: 8% ethyl cellulose, 3% soybean lecithin, 65% terpineol, and 24% butyl carbitol acetate. First, stir and heat the terpineol and soybean lecithin in a beaker to 70°C. Then, add ethyl cellulose and continue stirring until completely dissolved. Next, add butyl carbitol acetate and keep warm and stir for 30 minutes to obtain the organic carrier.
[0089] Preparation of the slurry: Raw materials were weighed according to the following mass percentages: 64% functional phase, 21% glass binder phase, and 15% organic carrier. The functional phase and glass binder phase were placed in an agate ball mill jar and mixed using alcohol as the medium. The mixture was ball milled at 250–300 r / min for 60–120 min. Afterward, the mixture was filtered, dried, and ground to obtain a uniformly dispersed powder. The powder was then premixed with the organic carrier in a planetary mixer at 1500–2000 r / min, and then thoroughly ground using a three-roll mill until the fineness was less than 5 μm, thus preparing the resistivity slurry of Comparative Example 6.
[0090] The resistance pastes of Examples 1-6 and Comparative Examples 1-6 were screen-printed onto alumina ceramic substrates, dried at 125°C for 10 minutes, and sintered in a belt tunnel sintering furnace at 850±10°C for 30 minutes with a peak holding time of 5 minutes to prepare test samples. The following performance tests were then conducted:
[0091] Sheet resistance: The sheet resistance is tested according to Method 105, Test Method for Sheet Resistance of Electronic Paste, in SJ / T11512-2015 Performance Test Method for Electronic Paste for Integrated Circuits.
[0092] TCR: According to the SJ / T11512-2015 Test Method for Performance of Electronic Paste for Integrated Circuits, Method 301 Test Method for Temperature Coefficient of Electronic Paste, the resistance values of the resistive element at 25℃, 125℃ and -55℃ are tested respectively.
[0093] The test results of the above embodiments and comparative examples are shown in Table 1.
[0094] Table 1 Comparison of Resistance Paste Performance
[0095] Example 1 0.10 36 17 19 Example 2 0.40 21 -6 27 Example 3 0.71 56 14 42 Example 4 0.44 52 -1 53 Example 5 0.32 67 22 45 Example 6 0.21 31 19 12 Comparative Example 1 0.42 89 12 77 Comparative Example 2 0.93 127 17 110 Comparative Example 3 0.98 106 15 91 Comparative Example 4 0.85 99 33 66 Comparative Example 5 0.98 105 23 82 Comparative Example 6 0.96 77 36 41
[0096] As can be seen from Table 1, the resistive pastes of Examples 1 to 6 of the present invention can obtain excellent ultra-low resistivity ruthenium-based resistive pastes with small temperature coefficient of resistance, sheet resistance below 1Ω / □, and high stability.
[0097] Comparing Example 1 with Example 6, and Comparative Example 2 with Comparative Example 6, it is shown that the addition of bismuth ruthenate will slightly increase the sheet resistance of the resistive slurry. When a large resistive slurry resistance is required, bismuth ruthenate can replace the role of ruthenium dioxide in the conductive functional phase. Under the same mass addition, the mass percentage of ruthenium in bismuth ruthenate is smaller, thereby saving the amount of precious metal ruthenium used.
[0098] Examples 1 and 5 were compared with Comparative Examples 1 to 6, and cross-sections were observed. Figure 1 ), simulation calculation ( Figure 2 The study used energy dispersive spectroscopy (EDS) to investigate the presence of silicon and silicon oxides dispersed within the silver and palladium layers. This indicates that silicon and silicon oxides can form solid solutions with palladium and silver, improving the silver migration problem at high temperatures and enhancing the thermal expansion properties of the conductive functional phase. Silicon can also react with the alumina substrate to form a transition structure between the conductive functional phase and the ceramic substrate, better connecting the conductive functional phase and the ceramic substrate. This not only solves the problem of matching the thermal expansion properties of the resistive element and the ceramic substrate from multiple perspectives but also increases the connection strength between the resistive element and the ceramic substrate, reducing the possibility of circuit relaxation, short circuits, or open circuits.
[0099] Examples 2-5 are compared with Comparative Examples 1-5 to demonstrate that when the metal cations of the added ruthenium salt in the ruthenium-based resistive paste are the same as those in the glass component (such as calcium ruthenium oxidase and calcium oxide in the glass binder phase), the ruthenium dioxide in the conductive functional phase and the glass binder phase are more closely connected by improving the interfacial properties of the conductive functional phase and the glass binder phase, resulting in a higher degree of matching. At the same time, it can obtain a stronger ability to regulate TCR than general metal oxides (such as copper oxide, zinc oxide, niobium pentoxide, etc.), resulting in a lower TCR value.
[0100] Example 5, compared with Comparative Examples 1 and 2, shows that the addition of copper oxide is more effective than the addition of zinc oxide in reducing the TCR value of the resistive paste, and its addition amount should not exceed 1%.
[0101] As can be seen from the above experimental results, the low TCR ultra-low resistance ruthenium-based resistive paste of the present invention, by changing the type and ratio of additives, changes the interface bonding mode between the conductive functional phase and the glass binder phase, and between the conductive functional phase and the ceramic matrix, which effectively reduces the resistance value and TCR, and to a certain extent reduces the cost, thus meeting the performance requirements of high-precision ultra-low resistance resistor products.
Claims
1. A low-TCR ultra-low-resistivity ruthenium-based resistive paste, characterized in that: The resistive paste, by weight percentage (100%), comprises: 50%–65% conductive functional phase, 15%–30% glass binder phase, 1%–5% additives, and 15%–30% organic carrier; wherein: The conductive functional phase is composed of silver, palladium, and bismuth ruthenium oxide; The additive is composed of titanium dioxide and any one of calcium ruthenate, copper ruthenate, and barium bismuthate. The glass binder phase comprises, by mass percentage (100%): SiO2 15%~90%, Al2O3 5%~75%, CaO 3%~25%, MgO 0%~1.5%; the softening temperature of the glass binder phase is 830~870℃ and the particle size is <5µm. Based on a mass percentage of 100%, the conductive functional phase consists of 85%~95% silver and palladium and 5%~15% bismuth ruthenate, wherein the particle size of the bismuth ruthenate is <50nm and the particle size of the silver and palladium is <2µm.
2. The low TCR ultra-low resistivity ruthenium-based resistive paste according to claim 1, characterized in that: Based on a mass percentage of 100%, the silver and palladium comprise 50% to 70% silver and 30% to 50% palladium.
3. The low TCR ultra-low resistivity ruthenium-based resistive paste according to claim 1, characterized in that: Based on a mass percentage of 100%, the additives comprise: titanium dioxide 30% to 50%, and any one of calcium ruthenate, copper ruthenate, and barium bismuthate 50% to 70%.
4. A low-TCR ultra-low-resistivity ruthenium-based resistive paste according to any one of claims 1 to 3, characterized in that: Based on a mass percentage of 100%, the organic carrier comprises: 75%~90% organic solvent, 6%~10% thickener, and 1%~5% organic additive; The organic solvent is one or more of terpineol, butyl carbitol acetate, and butyl carbitol; the thickener is one or more of ethyl cellulose, alkyd resin, and acrylic resin; and the organic additive is one or more of soybean lecithin, Span-85, and oleic acid.
5. A method for preparing a low-TCR ultra-low-resistivity ruthenium-based resistive paste as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Preparation of functional phase: Silver, palladium, bismuth ruthenate, and the additives are ground and dispersed in the specified amounts to obtain the functional phase; (2) Preparation of glass binder phase: Weigh SiO2, Al2O3, CaO and MgO raw materials according to the amount, mix the raw materials evenly and then melt them. The mixture is then quenched in water to obtain glass slag. The glass slag is ball-milled and dried to obtain glass binder phase. (3) Preparation of organic carrier: Weigh the organic solvent, thickener and organic additive according to the specified amount, and obtain the organic carrier by heating, dissolving and stirring; (4) Preparation of slurry: Weigh the functional phase, glass binder phase and organic carrier according to the specified amount, put the functional phase and glass binder phase into an agate ball mill jar, use alcohol as the medium, and ball mill and mix them at 250~300 r / min for 60~120 min. Then filter, dry, grind and disperse to obtain a uniformly dispersed powder. Then premix the powder and organic carrier in a planetary mixer at 1500~2000 r / min, and grind them thoroughly with a three-roll mill until the fineness is less than 5µm to prepare the resistive slurry.
6. The application of a low TCR ultra-low resistance ruthenium-based resistive paste according to any one of claims 1 to 4 in high-precision ultra-low resistance resistor products.
Citation Information
Patent Citations
Thick-film resistor paste simultaneously applicable to aluminum oxide ceramic substrate and isolation dielectric layer
CN113643840A
Composition for resistor and resistor paste containing the same furthermore thick film resistor therewith
JP2018092730A
